The NLRP3 inflammasome modulates glycolysis by increasing PFKFB3 in an IL-1Î²-dependent manner in macrophages - Lynch, Marina; Finucane, Orla; Guillot-Sestier, Marie-Victoire (My University, 2019)
Infammation and metabolism are intricately linked during infammatory diseases in which activation of the nucleotide-binding domain–like receptors Family Pyrin Domain Containing 3 (NLRP3) infammasome, an innate immune sensor, is critical. Several factors can activate the NLRP3 infammasome, but the nature of the link between NLRP3 infammasome activation and metabolism remains to be thoroughly explored. This study investigates whether the small molecule inhibitor of the NLRP3 infammasome, MCC950, modulates the lipopolysaccharide (LPS) -and amyloid-β (Aβ)- induced metabolic phenotype and infammatory signature in macrophages. LPS+Aβ induced IL-1β secretion, while pre-treatment with MCC950 inhibited this. LPS+Aβ also upregulated IL-1β mRNA and supernatant concentrations of TNFα, IL-6 and IL-10, however these changes were insensitive to MCC950, confrming that MCC950 specifcally targets infammasome activation in BMDMs. LPS+Aβ increased glycolysis and the glycolytic enzyme, PFKFB3, and these efects were decreased by MCC950. These fndings suggest that NLRP3 infammasome activation may play a role in modulating glycolysis. To investigate this further, the efect of IL-1β on glycolysis was assessed. IL-1β stimulated glycolysis and PFKFB3, mimicking the efect of LPS+Aβ and adding to the evidence that infammasome activation impacts on metabolism. This contention was supported by the fnding that the LPS+Aβinduced changes in glycolysis and PFKFB3 were attenuated in BMDMs from NLRP3-defcient and IL-1R1-defcient mice. Consistent with a key role for PFKFB3 is the fnding that the PFKFB3 inhibitor, 3PO, attenuated the LPS+Aβ-induced glycolysis. The data demonstrate that activation of the NLRP3 infammasome, and the subsequent release of IL-1β, play a key role in modulating glycolysis via PFKFB3. Reinstating metabolic homeostasis by targeting the NLRP3 infammasome-PFKFB3 axis may provide a novel therapeutic target for treatment of acute and chronic disease.
PUBLISHED
Keywords: Infammatory diseases; Inflammation; Metabolism